Abs. Issue 1 (November 2015) - Babyshkina, N.; Vtorushin, S.; Patalyak, S.; Dronova, T.; Slonimskaya, E.; N.Cherdyntseva,
Abstract : Background: Tamoxifen, a selective estrogen receptor modulator, remains a standard of endocrine therapy for estrogen receptor alpha (ER α ) positive breast cancer (Goldhirsch et al., 2013). Despite well-known advantages of tamoxifen treatment, approximately one third of patients experience a relapse or disease progression due to tamoxifen resistance (Osborne et al., 2011). Identification of additional molecular markers associated with both ER genomic and non-genomic pathways could be very useful to help identify patients who will likely benefit from such endocrine treatment. The aim of the present study was to evaluate the influence of the distribution pattern of ER α expression as well as ESR1, TGF-βR1 and IGF-1R single nucleotide polymorphisms (SNPs) and the expression of growth factors receptors on disease progression in breast cancer patients of Russian Western Siberian population treated by adjuvant tamoxifen. Materials and methods: Formalin-fixed paraffin-embedded tumor tissue samples were retrospectively collected from 97 hormone receptor-positive breast cancer patients treated with adjuvant tamoxifen at the Tomsk Cancer Research Institute. Genotypes for ESR1 +30T>C (rs2077647), ESR1 2014G>A (rs2228480), IVS7+24G > A (rs334354) and IGF-1R (rs2016347) SNPs were detected by a TaqMan assay. The distribution patterns of ER α expression and EGFR, TGF- β R1, IGF-1R protein expression were determined using the immunohistochemistry. Patients who developed distant metastasis or recurrence after tamoxifen treatment during the follow-up period were defined as tamoxifen resistance (TR) group, while distant metastasis-free patients were analyzed as tamoxifen sensitive (TS) group. Results: We found that the heterogeneous distribution of ER α expression was statistically significant related with poor prognosis of tamoxifen treated patients ( p = 0.021). Similarly, we showed high EGFR expression in TR group compared to TS patients (80.0% vs. 41.9% respectively, p = 0.009). Additionally, EGFR expression and distribution pattern of ER α expression were significantly associated with response to tamoxifen and this association remained significant in both univariate and multivariate analysis. Our results demonstrate that the ESR1 2014A mutant allele carriers were more prevalent in TR patients than in TS group (26.3% vs. 8.0%, respectively, p = 0.009). Concerning the IGF-1R polymorphism, we found that TT homozygous carriers were more frequent in the TS group compared with TR group ( p = 0.043). A significant association between IVS7+24G > A SNP and high TGF- β R1 protein expression was observed ( p = 0.044). Nonetheless, among all studied polymorphisms only ESR1 2014G>A SNP was correlated with a heterogeneous distribution of ER α expression ( r = 0.353, p = 0.016). Conclusion: These data suggest that the distribution pattern of ER α expression, EGFR expression and ESR1 2014G>A genetic variation could be useful additional prognostic markers for hormone receptor-positive breast cancer patients treated with adjuvant tamoxifen.